The edge [videorecording (DVD)] - Mamet, David; Tamahori, Lee; Hopkins, Anthony, 1937-; Baldwin, Alec, 1958-; Macpherson, Elle, 1964- (Twentieth Century Fox Home Entertainment, 2010)
A model is accompanied to a photo shoot by her rich, much older husband. When their plane crashes in the middle of nowhere, a strong mind game erupts between her jealous husband and a young photographer as they try to get back to civilization.